Merebut Rumah Ikan: Konsepsi Terumbu Karang pada Masyarakat Pesisir di Desa Batu Ampar, Anambas - Ramadhan, Zakirul Hasri; Hambali, Hambali; Zuska, Firkawin (Universitas Cenderawasih, 2022)
The people of Batu Ampar Village often come into direct contact with coral reefs, resulting in activities that have a positive or negative impact on the coral reef ecosystem. The use of coral reefs as building materials has had an adverse effect on the sustainability of coral reefs. Massive use also has side effects on fishermen who live in Batu Ampar Village, making it difficult to find fish on the coast of Palmatak Island. The purpose of this research is to find out the activities and assumptions of the people of Batu Ampar Village on coral reefs which can be seen from the activities carried out by the community in their daily lives. This study uses a descriptive qualitative method, namely conducting research by describing the appropriate conditions in the field without any data manipulation. The data were obtained using the In-Depth Interview method, namely interviews conducted in depth with informal conditions without any pressure on the informants. Information obtained by the Snowball method, which is looking for data from many informants, then the data is used to find actual facts according to the conditions in the field. The results of the study show that the use of coral reefs has been carried out for a long time and has had a negative effect on fishing communities, this can occur due to a lack of supervision from the authorities so that people are free to carry out activities using coral reefs. However, with strict supervisors and the development of education in Batu Ampar Village, making the community understand the importance of maintaining the coral reef ecosystem, the community began to maintain the coral reef ecosystem, this can be seen from the use of traditional fishing rods that do not damage nature and the use of clumps as tools environmentally friendly fishing.